A fast contact detection method for ellipsoidal particles. (12th February 2021) - Kheradmand, Elham; Prudhomme, Serge; Laforest, Marc
Abstract: This paper presents a fast and robust algorithm for contact detection between elliptical and ellipsoidal particles. The algorithm belongs to the class of geometrical potential methods, which consider the solution of two minimization problems in order to determine a contact point between the particles. The efficiency of the algorithm relies on several ingredients, namely, a transformation that maps the pair of ellipses (ellipsoids) into an ellipse (ellipsoid) centered at the origin and a unit circle (sphere), the construction of an effective initial guess to the solution of the minimization problem, the use of Newton's method for the root finding problem, and the introduction of an additional constraint to guarantee convergence to the desired root. The performance of the new algorithm is compared with that of existing contact detection algorithms on large sets of randomly generated pairs of particles. In particular, the results from several numerical examples show that the present algorithm is several times faster than the existing algorithms for comparable accuracy.